Mengidentifikasi Faktor Penentu Keberhasilan Kritis untuk Meningkatkan Kepatuhan SLA pada Managed Print Services: Studi Kasus Berbasis ITIL di Sebuah Organisasi Sektor Publik - Irwan Bengkulah; Teguh Raharjo (Informatik : Jurnal Ilmu Komputer, 2026)
The adoption of Managed Services (MS) has become a key strategy for public sector organizations seeking to enhance operational efficiency and service quality. However, maintaining consistent Service Level Agreement (SLA) compliance remains a major challenge, particularly due to vendor delays and limited service visibility. This study aims to identify and prioritize the Critical Success Factors (CSFs) influencing SLA compliance within the Managed Print Services (MPS) environment of a public sector organization. Using a mixed-method approach, the research applies the Analytic Hierarchy Process (AHP) to evaluate four service success criteria and eight corresponding CSFs, validated through expert judgment from echelon-4 IT officials. The results indicate that Vendor Responsiveness (36.0%) and User Satisfaction (27.7%) are the most influential criteria, reflecting an organizational emphasis on external service quality and user value. At the CSF level, strategic management factors dominate: Planning (20.2%), Evaluation (18.3%), and Leadership (15.8%) emerge as the top contributors, whereas technical elements such as Troubleshooting (7.8%) and Team Performance (5.8%) rank lowest. These findings highlight that sustainable SLA compliance in the public sector relies primarily on strengthening governance and strategic oversight rather than operational execution. Accordingly, the study recommends enhancing structured planning and continuous evaluation mechanisms to ensure alignment between service delivery and user value, consistent with ITIL principles.